Peningkatan Industri Kreatif Produk Pangan Lokal di Kabupaten Sidrap - Mulyana Machmud; Ulfa Natsir; Hartati Hartati; Arifin Allu (Jurnal Mirai Management, 2021)
The data analysis technique in this study used a qualitative descriptive approach with field research methods and SWOT analysis methods. SWOT analysis is used to determine the strengths, weaknesses, opportunities, and threats of creative industrial production businesses based on local food potential in Kanyuara Village, Watang Sidenreng District, Sidrap Regency. The result of this research is the local food product development strategy and the creative industry strategy in Kanyuara Village, Watang Sidenreng Subdistrict, Sidrap Regency experiencing obstacles in the development process. Here are some alternative strategies for the creative industry players that are differentiation, intensive, and integrated. Among them, participating in training, improving product quality, collaborating with the government or related institutions, optimizing production activities, affordable prices, expanding marketing reach, using a marketing mix including halal products. Keywords: Local Food, SWOT Analysis, Jipang